PENAMBAHAN TEPUNG DAUN KELOR (Moringa oleifera) DENGAN VARIASI SUHU PENGERINGAN DAN KONSENTRASI UNTUK MENINGKATKAN NILAI GIZI TEMPE - Puyanda, Irvia Resti; Nanik Suhartatik; Vivi Nuraini; Istiqomah Setyorini (Fakultas Pertanian Universitas Alkhairaat Palu, 2023)
Tempeh is a food product made from fermented soybeans using a type of mold called (Rhizopus sp) and contains good nutrition for the health of human body. Likewise, moringa leaves contain useful nutrients such as high antioxidant and protein content. This research aimed to determine the chemical and sensory characteristics of tempeh with the addition of moringa leaf flour using variations in the drying temperature of moringa leaves and the concentration of moringa leaf addition to soybeans based on the highest antioxidant activity and consumer preference. This study used a 2 factorial (CRD). The first factor was the drying temperature of moringa leaves and the second factor was the concentration of the addition of moringa leaf powder. Parameters observed in this study included chemical analysis, physical analysis and organoleptic test analysis. The best research result was at the drying temperature of moringa leaves at 40°C and the addition of moringa leaf powder with a concentration of 9%. From the results of the analysis, it was identified that the water content was 63,03%; the fat content was 0,98%; the protein content was 23,13%; the antioxidant activity was 58,72%; the pH was 5,70. Based on the physical analysis of this treatment, the tempeh had greenish spots from the tempeh and mold or mycelium which were white in color and have a compact texture. Meanwhile, the organoleptic test included the color of 1,54, the moringa leaf aroma of 1,53, the tempeh aroma of 3,64, the tempeh taste of 2,99.